2010
DOI: 10.1007/s10815-010-9463-y
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen decreases ovarian follicular loss from experimental toxicant DMBA and chemotherapy agents cyclophosphamide and doxorubicin in the rat

Abstract: tamoxifen decreases follicle loss and improves reproductive function following exposure to ovarian toxicants including chemotherapy drugs in the female rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 37 publications
7
42
1
1
Order By: Relevance
“…In an effort to replicate such findings, we performed a series of experiments under the exact same conditions as Johnson et al Our results confirmed those previously reported by us [26], [27], [28], [29] and others [29], [30], [31], [32] in that DXR causes depletion of the primordial follicle pool in a time dependent manner (Fig. 1A&B).…”
Section: Resultssupporting
confidence: 89%
“…In an effort to replicate such findings, we performed a series of experiments under the exact same conditions as Johnson et al Our results confirmed those previously reported by us [26], [27], [28], [29] and others [29], [30], [31], [32] in that DXR causes depletion of the primordial follicle pool in a time dependent manner (Fig. 1A&B).…”
Section: Resultssupporting
confidence: 89%
“…Several molecular pathways are involved in apoptosis of oocytes, including damage to chromosomes, activation of mitochondria and elevation of superoxides that induces endoplasmic reticulum stress with the increase in intracellular Ca ++ . This cascade in turn leads to apoptosis via calpain and caspase 12 [130][131][132][133] GCs DNA damage and apoptotic cell death induced by doxorubicin has been demonstrated both in human primordial follicles and GCs in vitro [134] Stromal cells/vessels Acute reduction in ovarian blood flow and disintegration of the vessel wall following in vivo administration of doxorubicin [30,135] Taxanes Mature follicles Only preclinical studies on taxane-induced ovarian toxicity are available, limiting to paclitaxel. The drug induces apoptosis mainly in mature follicles and to a lesser extent in less mature populations; also estradiol serum levels were reduced by the drug [136] 5-Fluorouracil Unknown Ovarian function in mice may be affected (reduced fertility) when the drug is administered during the immediate postovulatory phase, but not during the other phases of fertility cycle [137] AMH, anti-müllerian hormone; ECs, endothelial cells; GCs, granulosa cells; PMF, primordial follicles; TCs, theca cells.…”
Section: Mechanism(s) Of Ovarian Toxicity/features Of the Damage Refementioning
confidence: 99%
“…11 This study provides an important step toward animal models of combined chemotherapy regimens. Advancing toward the goal of cross-chemotherapy ovoprotection, tamoxifen shields the ovary from both cyclophosphamide (in vivo) and doxorubicin (in vitro).…”
Section: Rodent Studies Of Ovarian Chemotherapy Toxicity Compared To mentioning
confidence: 99%